2021
DOI: 10.21203/rs.3.rs-829214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mutations that adapt SARS-CoV-2 to mustelid hosts do not increase fitness in the human airway.

Abstract: SARS-CoV-2 has a broad mammalian species tropism infecting humans, cats, dogs and farmed mink. Since the start of the 2019 pandemic several reverse zoonotic outbreaks of SARS-CoV-2 have occurred in mink, one of which reinfected humans and caused a cluster of infections in Denmark. Here we investigate the molecular basis of mink and ferret adaptation and demonstrate the spike mutations Y453F, F486L, and N501T all specifically adapt SARS-CoV-2 to use mustelid ACE2. Furthermore, we risk assess these mutations and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…This is evident in our data; the increase in mouse ACE2 receptor usage by delta spike, albeit to a lesser extent than the N501Y-containing VOCs, suggests that changes in host tropism are likely a combinatorial effect of different RBD mutations. We observed a similar trend during adaptation of SARS-CoV-2 in ferrets, with spike mutations Y453F, F486L and N501T leading to increased ferret ACE2 usage [10]. This mirrors the situation with natural infections in mink, a related mustelid, where a similar array of mutations has repeatedly arisen [28, 29], leading to severe restrictions on the farming of mink and the mass culling of animals.…”
Section: Full-textmentioning
confidence: 70%
See 3 more Smart Citations
“…This is evident in our data; the increase in mouse ACE2 receptor usage by delta spike, albeit to a lesser extent than the N501Y-containing VOCs, suggests that changes in host tropism are likely a combinatorial effect of different RBD mutations. We observed a similar trend during adaptation of SARS-CoV-2 in ferrets, with spike mutations Y453F, F486L and N501T leading to increased ferret ACE2 usage [10]. This mirrors the situation with natural infections in mink, a related mustelid, where a similar array of mutations has repeatedly arisen [28, 29], leading to severe restrictions on the farming of mink and the mass culling of animals.…”
Section: Full-textmentioning
confidence: 70%
“…To support these research endeavours, we and others have shown that the SARS-CoV-2 spike has a broad tropism for mammalian ACE2 proteins [7–9]. Using lentiviral pseudotyping combined with live virus experiments, we showed that SARS-CoV-2 can use a wide range of mammalian ACE2s, including dog, cat, cattle, sheep, pangolin and rabbit, but is restricted with rat, ferret and a subset of bat and bird receptors [7, 10].…”
Section: Full-textmentioning
confidence: 99%
See 2 more Smart Citations
“…Wuhan-Hu-1-D614G with R203K/G204R was achieved by introducing mutations R203K (G28881A, G28882A) and G204R (G28883C). Reverse genetics (RG) derived viruses were generated essentially as previously described (76,77). Rescued RG SARS-CoV-2 viruses were sequenced using Oxford Nanopore as previously described (78).…”
Section: Infections In Calu-3 Cells With Sars-cov-2 Variantsmentioning
confidence: 99%